Pengaruh Gaya Kepemimpinan dan Budaya Terhadap Kinerja Karyawan pada PT. Pondok Indah Padang Golf - Satria Al-Fadli; Cecep Haryoto (Jurnal Ilmiah Manajemen, Bisnis dan Kewirausahaan, 2026)
This research aims to test and analyze the influence of Leadership Style and Organizational Culture on Employee Performance at PT Pondok Indah Padang Golf. The independent variables used are leadership style and organizational culture, while the dependent variable is performance. Method The data collection method in this research was carried out by distributing questionnaires to 65 employee respondents at PT Pondok Indah Padang Golf. The research method used is a quantitative method that is associative in nature using primary data. These results show that leadership style has a significant influence on employee performance with a calculated t value greater than t table 3.207 > 1.998 and a significant value of 0.02 < 0.05, organizational culture has a significant influence on employee performance with a calculated t value of more The size of the t table is 4.695 > 1.998 and the significant value is 0.00 < 0.05. Together, leadership style and organizational culture have a significant effect on employee performance with a calculated F value greater than F table 55.873 > 3.15 and a significant value 0.00 < 0.05.